Essays on firm finance, performance and growth: the case of selected African countries - Nyanchama, Arisa Linet (My University, 2019)
Adequate financing both to individuals and firms is very important since it spurs the development of a productive private sector, which creates employment opportunities and increase tax contribution for public investment, thereby promoting growth and development.
A thesis submitted in fulfilment to the degree of Doctor of Philosophy to the Faculty Commerce, Law and Management, in the School of Economic and Business Sciences University of the Witwatersrand